2019
DOI: 10.1002/mrc.4829
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of gluten‐free bread crumb baked at atmospheric and reduced pressures using TD‐NMR

Abstract: This research aimed to study the effects of using a partial vacuum for bread baking on macromolecules and water distribution in gluten‐free bread. Bread baking under partial vacuum results in greater oven rise and a larger gas fraction in the crumb. Because water's boiling point decreases under reduced pressure, it was expected that its distribution within the dough and its interactions with the others dough's constituents (mainly starch) would differ from those in bread baked under atmospheric pressure. Time‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…This method is commonly used to determine the diffusion of water and oils within liquid, gel, and even solid materials. 29, 30…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method is commonly used to determine the diffusion of water and oils within liquid, gel, and even solid materials. 29, 30…”
Section: Resultsmentioning
confidence: 99%
“…TD-NMR is a technique used commonly in food science and hydrogel research to determine the diffusion of water and oils in liquid, gel, and even solid states. 34,35 In this work, diffusion coefficients of water molecules in protein solutions are represented relative to the diffusion coefficient of the water molecules in bulk solution of the buffer used in each experiment (water alone or 20 mM Tris), in order to emphasize the differences between proteins. This is calculated as (Buffer Diffusion − Protein Diffusion) and is referred to as Δ Diffusion Coefficient (ΔDC).…”
Section: Cahs D Gelation Slows Diffusion In a Hydrated State And Immobilizes Biological Materialsmentioning
confidence: 99%
“…Hydrothermal treatments, extrusion, high-pressure baking, ultrasound aeration (Naqash et al 2017), microwave-assisted baking and low-pressure (vacuum) baking (Rondeau-Mouro et al 2019) are novel technologies that have been applied to improve the quality and storage https://doi.org/10.17221/180/2022-CJFS properties of gluten-free bread (Tuta Şimşek 2020). It was reported that using a vacuum in conventional baking resulted in a softer bread product than traditional methods during yeast-free bread production using supercritical fluid extrusion of dough (Ruttarat-tanamongkol et al 2011;Rondeau-Mouro et al 2019). A combination of them can be applied to increase the potential of non-conventional baking techniques while minimising the disadvantages (Dapčević-Hadnađev et al 2022).…”
Section: Technological Strategies Applied To Baking and For Extending...mentioning
confidence: 99%
“…Carini et al (2017) additionally evaluated changes to the molecular behavior in gluten-free bread formulations showing that the extent of typical storageassociated changes to proton distribution (e.g., decrease in T 2 relaxation time of population B) differed based on the bread formulation. Recently, Rondeau-Mouro et al (2019) evaluated molecular mobility and water distribution in gluten-free breads baked either at atmospheric pressure or under partial vacuum and assessed differences therein throughout 4 days of staling.…”
Section: 1mentioning
confidence: 99%
“…Recently, Rondeau‐Mouro et al. (2019) evaluated molecular mobility and water distribution in gluten‐free breads baked either at atmospheric pressure or under partial vacuum and assessed differences therein throughout 4 days of staling.…”
Section: Td 1h Nmr As a Tool To Study Gluten‐free Food Formulationsmentioning
confidence: 99%